2017
DOI: 10.1007/s00431-017-2972-2
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: probiotics for functional constipation in children

Abstract: We updated our 2010 systematic review on the efficacy of probiotics in the treatment of constipation in children. The MEDLINE, EMBASE, and Cochrane Library databases; clinical trial registries; and reference lists of included studies were searched to February 2017 for randomized controlled trials (RCTs) performed in children, with no language restriction. The primary outcome measure was treatment success, as defined by the investigators. We included seven RCTs with a total of 515 participants. Included trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 30 publications
(68 reference statements)
0
62
0
7
Order By: Relevance
“…Beyond the antipathogenic properties of Lcr35 ® , recent studies in humans have shown improvement in the health of patients with the administration of LBM. The effectiveness of Lcr35 ® for the treatment of abdominal pain and intestinal functional disorders has been demonstrated in children [22][23][24] without however highlighting the molecular mechanisms. Recently, Dausset and colleagues demonstrated in women the safety and well-tolerated characteristics of a new galenic form based on Lcr35 ® , promoting the growth of endogenous vaginal Lactobacillus, in order to prevent an eventual dysbiosis [25].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the antipathogenic properties of Lcr35 ® , recent studies in humans have shown improvement in the health of patients with the administration of LBM. The effectiveness of Lcr35 ® for the treatment of abdominal pain and intestinal functional disorders has been demonstrated in children [22][23][24] without however highlighting the molecular mechanisms. Recently, Dausset and colleagues demonstrated in women the safety and well-tolerated characteristics of a new galenic form based on Lcr35 ® , promoting the growth of endogenous vaginal Lactobacillus, in order to prevent an eventual dysbiosis [25].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review included seven RCTs enrolling a total of 515 children that investigated the effects of probiotics in pediatric FC. Although two of the included studies, those evaluating L. reuteri DSM 17938 165 and B. longum 166 , reported significantly increased defecation frequency in the treatment arm, the meta-analysis concluded that there is currently insufficient evidence to support the use of probiotics for pediatric FC 167 . Finally, although a low-fiber diet is a known risk factor for FC in children 168 , there is currently little evidence to support the use of fiber for pediatric FC.…”
Section: Functional Gi Disordersmentioning
confidence: 97%
“…In the literature, five systematic review articles were found, 30,[33][34][35][36] Two had a meta-analysis, 30,34 which addressed the use of probiotics in the treatment of functional constipation in children and adolescents. An article published in 2010 33 included two clinical trials in children 18,21 and three adult trials, and concluded that only L. rhamnosus Lcr35 showed a beneficial effect for the treatment of constipation in children.…”
Section: Lactobacillus Casei Rhamnosus Lcr35mentioning
confidence: 99%
“…A systematic review published in 2016 35 on the use of prebiotics, probiotics and symbiotics for the treatment of functional constipation in children concluded that there is still insufficient evidence to support the recommendation of probiotics in this treatment. At the same time as the present article was being completed, two systematic reviews were published 30,36 addressing this theme. In 2017, a systematic meta-analysis review highlighted the effectiveness of probiotics for improving bowel movement frequency in Asian children, and highlighted the heterogeneity of the studies.…”
Section: Lactobacillus Casei Rhamnosus Lcr35mentioning
confidence: 99%
See 1 more Smart Citation